2006
DOI: 10.1103/physreva.74.023201
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb explosion of hydrogen clusters irradiated by an ultrashort intense laser pulse

Abstract: The explosion dynamics of hydrogen clusters driven by an ultrashort intense laser pulse has been analyzed analytically and numerically by employing a simplified Coulomb explosion model. The dependence of average and maximum proton kinetic energy on cluster size, pulse duration, and laser intensity has been investigated respectively. The existence of an optimum cluster size allows the proton energy to reach the maximum when the cluster size matches with the intensity and the duration of the laser pulse. In orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…If something induced a breakup of clusters causing a drop in average ion energy at the highest intensities, it certainly did not appreciably affect the Coulomb nature of the expansion at the optimum intensity of 2.8×10 16 W/cm 2 . It has been speculated that once the laser field is intense enough to strip all electrons from a given cluster, the cluster would also experience total outer ionization for electric fields of even greater intensity, resulting in similar ion kinetic energies [12,21]. According to our measurements, this was not the case and much less energetic ions (∼3 keV) were produced at the highest laser intensities near 1×10 18 W/cm 2 .…”
mentioning
confidence: 57%
“…If something induced a breakup of clusters causing a drop in average ion energy at the highest intensities, it certainly did not appreciably affect the Coulomb nature of the expansion at the optimum intensity of 2.8×10 16 W/cm 2 . It has been speculated that once the laser field is intense enough to strip all electrons from a given cluster, the cluster would also experience total outer ionization for electric fields of even greater intensity, resulting in similar ion kinetic energies [12,21]. According to our measurements, this was not the case and much less energetic ions (∼3 keV) were produced at the highest laser intensities near 1×10 18 W/cm 2 .…”
mentioning
confidence: 57%
“…The situation is more favorable in condensed media such as fused silica (SiO 2 ), where a broad spectral bandwidth of negative GVD extending over more than 2000 nm beyond 1.26 m is available. Several authors have performed numerical simulations of the propagation of IR laser pulses in fused silica [11][12][13]. On the experimental side, measurements in fused silica have shown that the critical threshold for filamentation is reduced [12] and that a broad conical continuum emission is produced [14,15], suggesting efficient pulse self compression.…”
mentioning
confidence: 99%
“…The propagation of intense few-cycle laser fields in a dispersive medium can be described by using a propagation equation in an axial-symmetric coordinates [42], 1) whereẼ(r, z, ω) is the frequency domain laser field, the nonlinear polarizatioñ P NL accounts for the Kerr effect and the polarizationJ ioni is caused by photoelectrons from the tunneling ionization of N 2 and O 2 in air. The collective motion of the tunneling ionized electrons results in a directional nonlinear photocurrent surge described by [11] ∂ t J e (r, z, t) + ν e J e (r, z, t) = e 2 m ρ e (r, z, t)E(r, z, t), (8.2) where ν e , e, m and ρ e denote the electron-ion collision rate, electron charge, mass, and electron density, respectively.…”
Section: Simulation Of Thz Emission In Air Plasma By a Few-cycle Pulsesmentioning
confidence: 99%
“…Interacting with a nonlinear medium, the variation of CEP becomes more complex because of the dispersion of the medium and the plasma effect. Taking the N 2 molecules (with the peak pressure of 100 torr, thickness of 1 mm) ionized by the intense few-cycle laser fields (with the pulse energy of 4 μJ and assuming the diameter of filament is 140 μm), the CEP shift over the interaction length is calculated by solving the propagation equation [42] and plotted in Fig. 8.9b.…”
Section: Initial Cepmentioning
confidence: 99%